ISLAMIC RELIGIOSITY TOWARD ACADEMIC FRAUD STUDENT OF UIN RADEN FATAH PALEMBANG - Muhamad Uyun (Psikis : Jurnal Psikologi Islami, 2020)
The goal of this research is to discover the relations between Islamic religiosity toward academic fraud of student of UIN Raden Fatah Palembang. The research is quantitative research. Subjects of the research are 204 students of UIN Raden Fatah Palembang. The hypothesis in this research there is a relationship between islamic religiosity towards academic fraud. Data collection uses 2 measurements,namely 1) Islamic religiosity using Psychological Measure of Islamic Religiousness (PMIR) scale; 2) Academic fraud using self reporting cheating scale (SRCS). Prerequisite test using Goodness of Fit Overall showing that from 5 criterias show good model. Analysis results by using SEM from 8 religiosity dimensions, 7 dimensions not proven so that there is no significant relationship between islamic religiosity towards academic fraud. One dimension significantly proven is dimension of religious anxiety.